School readiness measurement: an implementation of the nijmeegse schoolbekwaamheids test (NST) - Ramadhini, Fitri; Nasution, Elsa Mutiah (Universitas Islam Negeri Raden Intan Lampung, 2022)
Preparing children to enter elementary school is an important thing that must be known and understood by parents. Choosing to send children to school too early without paying attention to their ability and development will cause a fatal impact. Readiness for early childhood schools is certainly different from one child to another. Still, the readiness of children can be seen from the maturity of the different aspects of physical, motoric, cognitive, social, and emotional development that will directly help children in the learning process and adjust to their school environment. This research is a descriptive quantitative study to see the implementation of the Nijmeegse Schoolbekwaamheids Test (NST) as one of the various test tools to measure the readiness of a child to enter elementary school. The results and research findings get the readiness of children to enter elementary school is not only assessed from the age factor. The readiness of children to enter elementary school is assessed by motor skills, observation skills, concentration abilities, understanding abilities, and the ability to assess situations.